Real-world use of ranibizumab for neovascular age-related macular degeneration in Taiwan - Yi-Sheng Chang (Nature Portfolio, 2018)
Abstract This study investigated the “real-world” use of ranibizumab for neovascular age-related macular degeneration (nAMD) in Taiwan and assessed the visual outcome. We reviewed the medical records at National Cheng Kung University Hospital, Taiwan, during 2012–2014 for 264 consecutive eyes of 229 patients with nAMD, who applied for ranibizumab covered by national health insurance. A total of 194 eyes (73.5%) in 179 patients (65.5% men; mean ± standard deviation age 69.4 ± 10.7 years) were pre-approved for treatment. Applications for treatment increased year by year, but approval rates decreased during this time. The major causes of rejection for funding were diseases mimicking nAMD, including macular pucker/epiretinal membrane, macular scarring, dry-type AMD, and possible polypoidal choroidal vasculopathy. After completion of three injections in 147 eyes, visual acuity significantly improved, gaining ≥1 line in 51.8% of eyes and stabilising in 38.3% of 141 eyes in which visual acuity was measured. The 114 eyes approved with only one application had a better visual outcome than the 27 eyes approved after the second or third applications. In conclusion, ranibizumab is effective for nAMD; however, approval after the second or third application for national health insurance cover is a less favourable predictor of visual outcome.